Castle of Ballylaghan, South West: Aspect: Co Carlow Augst: 7th: 1792. - Grose, Daniel, approximately 1766-1838 (1792)
There seems to be confusion over the name and place of this castle (see notes in 2122 TX (3) 16). It is probably Ballyloughan Castle, County Carlow, Ireland.
Engraving of this drawing by J. Newton and published by S. Hooper, August 1792, as Plate 3 in Volume II of "The Antiquities of Ireland" by Francis Grose (publishers: Samuel Hooper, No. 212 High Holborn, London, 1794).
Inscribed in ink u.l. on verso: No. 71.
Title inscribed in ink on verso.
Watermark visible l.r. with the letters "JW". This could be part of the name "J Whatman".
Irish topographical prints & drawings / Rosalind M. Elmes. - Malton Press, Dublin, 1975
Keywords: Ballyloughan Castle (Carlow, Ireland) -- 1790-1800.; Castles & palaces -- Ireland -- Carlow (County) -- 1790-1800.; Ink drawings -- Irish -- 1790-1800.; Wash drawings -- Irish -- 1790-1800.